VARIABILITAS pH TANAH DI LAHAN PERCOBAAN UNIVERSITAS BINA INSAN, LUBUKLINGGAU - mashum, Halim (LPPM Universitas Bina Insan, 2024)
As a growing medium, soil plays a crucial role in supporting the growth and development of plants on its surface. Analyzing soil properties is a necessary preliminary step before planting. pH (Potential of Hydrogen) is one of the essential soil properties that supports plant growth and development. Soil pH conditions can affect the availability of nutrients in the soil and the level of nutrient uptake by plants. The methods used in this research are survey and field observation. Sampling points were determined through spatial analysis using ArcMap 10.8. Soil sampling was conducted using the grid sampling method with a 20x20 m plot. The results of the study indicate that land use has an impact on soil pH conditions. Open land has the lowest soil pH compared to other land uses. Strategies that can be implemented to increase soil pH include: the application of soil amendments, practicing minimum tillage, and increasing land cover.